The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/ange.201200346
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Aromatic Compounds by π Pocket within a Cage‐Shaped Borate Catalyst

Abstract: Die Arylsubstituenten am Borzentrum des käfigförmigen Borats B(OC6H3Aryl)3CH bilden eine π‐Tasche (siehe Bild), sodass dieses zwischen Substraten mit verschiedenen Kohlenwasserstoffgerüsten unterscheiden kann. Der Lewis‐Säure‐Katalysator aktiviert aromatische Aldehyde viel stärker als aliphatische.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…38 In the synthesis of a cage-shaped boron catalyst, Yasuda and Baba used BH 3 •THF as the boron source to react with a triphenol that bears recognition sites (2-naphthyl) for aromatic aldehydes (Scheme 19). 39 41 These compounds can serve as sensing indicators for the pH and anions in mineral waters. Further studies showed that they also exhibit light-harvesting abilities in the visible wavelength region, thus having potential utilities in dye-sensitized solar cells.…”
Section: Natural Products and Bioactivementioning
confidence: 99%
“…38 In the synthesis of a cage-shaped boron catalyst, Yasuda and Baba used BH 3 •THF as the boron source to react with a triphenol that bears recognition sites (2-naphthyl) for aromatic aldehydes (Scheme 19). 39 41 These compounds can serve as sensing indicators for the pH and anions in mineral waters. Further studies showed that they also exhibit light-harvesting abilities in the visible wavelength region, thus having potential utilities in dye-sensitized solar cells.…”
Section: Natural Products and Bioactivementioning
confidence: 99%